Analysis of Factors that Influence Student Learning Achievement - Lastri, Lastri; Kartikowati, Sri; Sumarno, Sumarno (Journal of Educational Sciences, 2020)
This study aims to analyze the factors that affect student achievement in the Department of Economic Education at the Faculty of Tarbiyah and Teacher Training of UIN Suska Riau. Population of this study was 201 students with a sample of 100 people. Data collected using questionnaire and documentation instrument. The data analysis technique used multiple regression analysis. The results showed that learning motivation has a positive and significant effect on learning achievement. The learning interest has a positive and significant effect on learning achievement. The family environment has a positive and significant effect on learning achievement, and teh learning motivation has also a positive and significant effect on learning achievement. There is a joint influence of learning motivation, interest in learning, family environment and learning models, together on learning achievement.